PEPFAR Funding and Reduction in HIV Infection Rates in 12 Focus Sub-Saharan African Countries: A Quantitative Analysis - Roger J. Chin, MA, MPA; Domrongphol Sangmanee, MA; Lisa Piergallini, MA (Global Health and Education Projects, Inc., 2015)
Background: HIV and AIDS continue to have a calamitous effect on individuals living on the continent of Africa. U.S. President George W. Bush implemented the President's Emergency Plan for AIDS Relief (PEPFAR) with the objective of committing approximately $15 billion from 2004 through 2008 to assist with the reduction of the HIV pandemic worldwide. The majority of the PEPFAR policy and funding focused on 12 countries in sub-Saharan Africa: Botswana, Cote d'Ivoire, Ethiopia, Kenya, Mozambique, Namibia, Nigeria, Rwanda, South Africa, Tanzania, Uganda, and Zambia. The policy question this research paper seeks to analyze is whether the PEPFAR funding (as a % of Gross Domestic Product (GDP)) allocated to the 12 countries in Africa had any effect on the decrease of HIV infection rates of males and females between the ages of 15 and 49. Methods: A fixed-effects panel regression analysis was conducted to determine if this association exists. This study examined the 12 African countries that received PEPFAR funding over the years 2002 to 2010; even though PEPFAR was only active from 2004 through 2008, this research included two years prior and two years after this timeframe in order to better estimate the effect of PEPFAR funding on HIV reduction. Results: The results illustrate that on average, ceteris paribus, for every 1 percentage point increase in PEPFAR funding per GDP a country received, the country's HIV infection rate decreased by 0.355 percentage points. Conclusions and Global Health Implications: While the empirical findings in this study suggested that the correlation between PEPFAR funding and HIV reduction is statistically significant, the practical significance is perhaps less obvious. Arguably, the reduction rate should be higher given the extent of funding targeted to this project. The conclusion of this research provides suggestions on future research and the policy implications of PEPFAR.